The Short-Term Causality Management Between Economic Growth and Excise Revenue: Review of Economic Regulation and Accounting Best Practice - Budi Laksono, Agung; Adha, Wahyu Maulid; Hartoto, Hartoto; Buniarto, Edwin Agus; Widada, Rasyid (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study aims to find the Granger causality between economic growth and excise revenue. Does economic growth drive the increase in excise revenue, or vice versa, does excise revenue drive the increase in economic growth? To conduct this test, the Granger causality test is used. Observations were made from 1998 to 2018. This observation period was made considering that 1998 was the year after the economic crisis and 2018 was the last year the excise tariff policy was in effect before it became effective in 2019. Data sources were obtained from the government's state budget financial records. The results obtained are that there is no Granger causality between excise revenue (Xt) and economic growth (Yt), but on the contrary, there is a Granger causality between economic growth (Yt) and excise revenue (Xt). However, the performance of current excise revenue (Xt) is affected by the performance of excise revenue in the previous year (Xt-1), while the performance of excise revenue two years earlier (Xt-2) does not affect excise revenue this year (Xt). Similarly, economic growth in the previous year (Yt-1) also has no significant effect on this year's excise revenue (Xt).